HPTLC Fingerprint Profile and Identification of Antidiabetic and Antioxidant Leads from Bauhinia rufescens L - Wadah Osman; Mona S Mohammed; Hassan S Khalid; Abdelkhalig Muddathir; Shaza W. Shantier; Bashier Osman; Iman Abdoon (Hindawi Limited, 2020)
Diabetes is one of the world's major health problems, and many reports have supported the role of oxidative stress in the pathogenesis of both type 1 and type 2 diabetes. The present study aims to evaluate the antidiabetic and antioxidant activity of Bauhinia rufescens, a plant used in Sudanese folkloric medicine for the treatment of diabetes. It was also aimed to identify isolates and characterize the bioactive antidiabetic and antioxidant compounds using bioactivity-guided fractionation followed by high-performance thin-layer chromatography (HPTLC) autobiography, liquid chromatography-mass spectrometric analysis, and nuclear magnetic resonance (NMR). Two potential compounds were successfully isolated and identified which may provide new leads for more potent analogues in drug discovery.